Prompt recognition of infectious pulmonary tuberculosis is critical to achieving elimination goals: a retrospective cohort study. Issue 1 (24th May 2020) - Heffernan, Courtney; Barrie, James; Doroshenko, Alexander; Egedahl, Mary Lou; Paulsen, Catherine; Senthilselvan, Ambikaipakan; Long, Richard
Abstract : Introduction: All pulmonary tuberculosis (PTB) cases are presumed to be infectious to some degree. This spectrum of infectiousness is independently described by both the acid-fast bacilli smear and radiographic findings. Smear-positive patients with chest radiographic findings that are typical for adult-type PTB are believed to be most infectious. Hypothesis: Characterisation of the presumed most infectious PTB case is possible by reference to readily available clinical features and laboratory results. Methods: Retrospective cohort study of adult, culture-positive PTB cases (151 smear-positive; 162 smear-negative) diagnosed between 1 January 2013 and 30 April 2017 in Canada. We describe cases according to demographic, clinical and laboratory features. We use multivariable multinomial logistic regression to estimate the relative risk ratio (RRR) with 95% CI of features associated with an outcome of smear-positive PTB, characterised by 'typical' chest radiograph findings. Results: Being Canadian-born, symptomatic, having a subacute duration of symptoms and broad-spectrum antibiotic prescriptions were all more commonly associated with smear-positive than smear-negative disease (36% vs 20%; 95% vs 63%; 88% vs 54%; and 59% vs 28%, respectively). After combining smear status and radiographic features, we show that smear-positive patients with typical chest radiographs were younger, had a longer duration of symptoms (RRR 2.41; 95% CI 1.01 to 5.74 and 2.93; 95% CI 1.20 to 7.11, respectively) and were less likely to be foreign-born, or have a moderate to high-risk factor for reactivation (RRR 0.40; 95% CI 0.17 to 0.92 and 0.18; 95% CI 0.04 to 0.71, respectively) compared with smear-negative patients with atypical chest radiograph findings. Conclusion: A clear picture of the presumed most infectious PTB case emerges from available historical and laboratory information; vigilance for this presentation by front-line providers will support elimination strategies aimed at reducing transmission.